Integration of BMP-2/PLGA microspheres with the 3D printed PLGA/CaSO4 scaffold enhances bone regeneration - Zhao, Li; Zhao, Xiaoliang; Deng, Fengpiao; Ye, Xiangling; Shen, Zhen; Xia, Yuanjun; Zhang, Ying (Frontiers in Materials, 2024)
Treatment of large and complex irregular bone defects is a major clinical challenge in orthopedic surgery. The current treatment includes bone transportation using the Ilizarov technique and bone cement repair using the Masquelet technique, but they require long-term manual intervention or secondary operation. To improve this situation, we compared the different implanting materials in the literature published in the past 10 years, finding that glycolic acid copolymer (PLGA) and Calcium sulfate (CaSO4) are appropriated to be used as synthetic bone materials due to their advantages of easy-availability, nontoxicity, osteogenic properties and rapid degradation. Meanwhile, the development of 3D printing technique and devices makes it relatively easier to synthetize customized bio-mimetic porous scaffolds, thus facilitating the release of modified protein. In this study, we compounded BMP-2/PLGA microspheres with polylactic glycolic acid copolymer/CaSO4 (PC) 3D printed scaffold to improve the osteogenic properties of the scaffold. The result of our in vitro experiment demonstrated that the prepared PCB scaffold not only had satisfactory bio-compatibility, but also promoted osteogenic differentiation. This 3D printed scaffold is capable to accelerate the repair of complex bone defects by promoting new bone formation, suggesting that it may prove to be a potential bone tissue engineering substitute.